A boy with conduct disorder (CD), attention deficit hyperactivity disorder (ADHD), borderline intellectual disability, and 47, XXY syndrome in combination with a 7q11.23 duplication, 11p15.5 deletion, and 20q13.33 deletion. Issue 1 (December 2016) - Kolaitis, Gerasimos; Bouwkamp, Christian; Papakonstantinou, Alexia; Otheiti, Ioanna; Belivanaki, Maria; Haritaki, Styliani; Korpa, Terpsihori; Albani, Zinovia; Terzioglou, Elena; Apostola, Polyxeni; Skamnaki, Aggeliki; Xaidara, Athena; et al.
Abstract Background This is a case with multiple chromosomal aberrations which are likely etiological for the observed psychiatric phenotype consisting of attention deficit hyperactivity and conduct disorders. Case presentation We report on an 11 year-old boy, admitted to the pediatric hospital for behavioral difficulties and a delayed neurodevelopmental trajectory. A cytogenetic analysis and high-resolution microarray comparative genomic hybridization (CGH) analysis was performed. The cytogenetic analysis revealed 47, XYY syndrome, while CGH analysis revealed an additional duplication and two deletions. The 7q11.23 duplication is associated with speech and language delay and behavioral symptoms, a 20q13.33 deletion is associated with autism and early onset schizophrenia and the 11p15.5 microdeletion is associated with developmental delay, autism, and epilepsy. The patient underwent a psychiatric history, physical examination, laboratory testing, and a detailed cognitive, psychiatric, and occupational therapy evaluation which are reported here in detail. Conclusions In the case of psychiatric patients presenting with complex genetic aberrations and additional psychosocial problems, traditional psychiatric and psychological approaches can lead to significantly improved functioning. Genetic diagnostic testing can be highly informative in the diagnostic process and may be applied to patients in psychiatry in case of complex clinical presentations.